Multipath geographic routing using false destinations. (29th June 2011) - De Caneva, D.; Montessoro, P.L.
This paper presents false destination forwarding (FDF), a technique that can be adopted for multipath routing in wireless sensor networks to avoid the overhead caused by the maintenance of disjointed or partially disjointed routing paths. FDF changes the packet destination target as the packet itself proceeds along the path: this way, it does not require any change to the underlying geographic routing protocols and can be implemented as an optional intermediate layer, built just above the geographic routing layer. Three different FDF strategies are discussed; they show good performance in simulations and can be effectively implemented in existing networks. FDF could disclose interesting opportunities for new multipath routing protocols, which might help solving the problem of reliability in wireless sensor networks in an efficient manner.